PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN KAHOOT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR AKUNTANSI SISWA KELAS XI SMKS PAB 2 HELVETIA - Maria Finsensia Sihaloho; Rini Herliani; Ramdhansyah Ramdhansyah; Pasca Dwi Putra; Choms Gary Ganda Tua Sibarani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the low motivation and accounting learning outcomes of eleventh-grade students at SMKS PAB 2 Helvetia, as indicated by limited participation in classroom activities, low learning enthusiasm, and the inability of many students to achieve the Minimum Learning Achievement Criteria (KKTP). The study aimed to improve students’ motivation and accounting learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by the Kahoot application. This research employed Classroom Action Research (CAR) conducted in two cycles involving 17 eleventh-grade accounting students as research subjects. Data were collected through observation, learning outcome tests, and documentation. The findings revealed that the implementation of the PBL model assisted by Kahoot significantly improved students’ learning motivation. In the first cycle, 10 students (58.8%) demonstrated good learning motivation, which increased to 14 students (82.4%) in the second cycle. This improvement was reflected in greater participation in discussions, increased confidence in asking questions, and higher enthusiasm during learning activities. Learning outcomes also improved substantially, with the percentage of students achieving mastery increasing from 29.4% (5 students) in the pre-test to 64.7% (11 students) in the first cycle and 88.2% (15 students) in the second cycle. Therefore, the Problem Based Learning model assisted by Kahoot proved effective in enhancing both learning motivation and accounting learning outcomes among eleventh-grade students at SMKS PAB 2 Helvetia. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya motivasi dan hasil belajar akuntansi peserta didik kelas XI SMKS PAB 2 Helvetia yang ditunjukkan oleh rendahnya keterlibatan dalam pembelajaran, kurangnya semangat belajar, serta belum tercapainya Kriteria Ketercapaian Tujuan Pembelajaran (KKTP) oleh sebagian besar siswa. Penelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar akuntansi melalui penerapan model Problem Based Learning (PBL) berbantuan media Kahoot. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus dengan melibatkan 17 peserta didik kelas XI Akuntansi sebagai subjek penelitian. Teknik pengumpulan data meliputi observasi, tes hasil belajar, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model PBL berbantuan Kahoot mampu meningkatkan motivasi belajar siswa. Pada siklus I, sebanyak 10 siswa (58,8%) menunjukkan motivasi belajar yang baik, kemudian meningkat menjadi 14 siswa (82,4%) pada siklus II. Peningkatan motivasi ditandai dengan bertambahnya keaktifan dalam diskusi, keberanian bertanya, dan antusiasme selama pembelajaran. Hasil belajar juga mengalami peningkatan, dari 5 siswa (29,4%) yang tuntas pada pre-test menjadi 11 siswa (64,7%) pada siklus I dan meningkat lagi menjadi 15 siswa (88,2%) pada siklus II. Dengan demikian, model Problem Based Learning berbantuan Kahoot terbukti efektif dalam meningkatkan motivasi dan hasil belajar akuntansi siswa kelas XI SMKS PAB 2 Helvetia.